2015
DOI: 10.1097/igc.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Plasma D-Dimer, Fibrinogen, and Platelet Levels Significantly Impact Prognosis in Patients With Epithelial Ovarian Cancer Independently of Venous Thromboembolism

Abstract: Pretreatment plasma D-dimer, fibrinogen, and platelet levels, which impact prognosis independently of VTE, were demonstrated to be potential markers to predict disease progression and surgery outcome in patients with EOC. The combined use of plasma D-dimer, fibrinogen, and platelet levels may help to identify the high-risk populations for treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 44 publications
2
73
0
1
Order By: Relevance
“…Plasma D-dimer levels have been shown to be increased in patients with gastric (29), colorectal (30), lung (31,32), ovarian (33) and breast cancer (34). Oya et al (13) demonstrated that D-dimer level is associated with the depth of tumor invasion at the time of surgical excision in patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma D-dimer levels have been shown to be increased in patients with gastric (29), colorectal (30), lung (31,32), ovarian (33) and breast cancer (34). Oya et al (13) demonstrated that D-dimer level is associated with the depth of tumor invasion at the time of surgical excision in patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, D‐dimer levels can be utilized as a predictor of immediate mortality in patients with in‐hospital cardiac arrest . An increasing body of evidence suggests the existence of a relationship between activation of coagulation and tumor angiogenesis, progression, and metastatic spread . Fibrinogen and D‐dimer levels are easily obtainable tests commonly ordered for inpatients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that plasma fibrinogen and/or D‐dimer levels can predict poor prognosis in several types of malignancies including ovarian, breast, colorectal, lung, gastric, and pancreatic cancer . In lung cancer, plasma fibrinogen and D‐dimer levels have been shown to be associated with tumor pathological stage, response to therapy, and survival .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations